(untitled) (GESTIÓN Y TENDENCIAS, 2020)
This article offers a look at the pension systems of Latin America and the Caribbean and the challenges they currently face. It also presents the work carried out by the IDB’s Pensions Network in Latin America and the Caribbean, which for more than four years has supported countries in the region in their ongoing effort to improve their pension systems. Finally, the article discusses the importance of voluntary pension saving in a context of demographic change and greater longevity.